Neonatal Morbidity in Term Newborns Born by Elective Cesarean Section - Resende, Maria Cristina (2015)
Introduction: International guidelines suggest that non-urgent planned deliveries be scheduled at or after 39 weeks. Despite this recommendation elective cesarean often occurs before 39 weeks. Some research has demonstrated that elective cesarean before 39 weeks poses a greater risk to the infants than at or after 39 weeks.Objective: To evaluate neonatal morbidity in term newborns born by elective cesarean section.Material and Methods: Retrospective study of all term elective cesarean sections (scheduled and without labor) performed in level III maternity, in the last 11 years (2003 - 2013). High risk pregnancies were excluded: twins, premature rupture of membranes, preeclampsia, poorly controlled diabetes mellitus, Rh isoimmunization and congenital malformations. Two groups of newborns with gestational age less than 39 weeks and equal or greater than 39 weeks gestational age were compared.Results: In our sample, 45% of elective caesarean sections were performed before 39 weeks. Infants born before 39 weeks were more frequently admitted in neonatal intensive care, odds ratio 2.4 [1.4 – 4.1] p = 0.001, had more respiratory morbidity, odds ratio 2.4 [1.6 - 3.8] p < 0.001, more hyperbilirubinaemia odds ratio 2.3 [1.5 – 3.7] p < 0.001, more hypoglycaemia and/or feeding difficulties odds ratio 1.6 [1.2 – 2.4] p = 0.006, and longer admissions (more than five days), odds ratio 2.0 [1.4 - 3] p < 0.001.Discussion: As in other studies ‘early term’ had higher respiratory and metabolic morbidity and consequently had a longer hospital stay.Conclusion: These findings support recommendations to delay elective cesarean delay until 39 weeks of gestation.